An ARDL Approach in Food and Beverages Industry Growth Process in Malaysia - Kamaruddin, Rohana; Jusoff, Kamaruzaman (2009)
The study examines the process of growth in the value added of food and beverages industry in Malaysia. The per capita income, population, skill and export are likely to exhibit long run relationship with the value added growth of this industry. Using the newly developed autoregressive distributed lag (ARDL) by Pesaran et al, (1995,1997, 1999 and 2000), a long run steady state equilibrium relationship between the independent variables and the growth performances of food industries is detected. Specifically this study has shown that in addition to the size of the population and percapita income, export are closely related to the growth of the value added of food and beverages industry. This empirical result would help Malaysia aspiration of becoming a hub for the halal food industry a reality.